STRATEGI PENINGKATAN PLACE BRANDING POKDARWIS KAMPOENG HERITAGE KAJOETANGAN MELALUI PELATIHAN PEMASARAN SECARA VIRTUAL - Zahro Zainal Abidin; Sri Mangesti Rahayu; Maria Goretti Wi Endang Nirowati Pamungkas; Rachma Bhakti Utami (Universitas Mataram, 2022)
Kampoeng Heritage Kajoetangan is one of the potential locations for tourism development in Malang City, especially cultural tourism. This location has heritage and historical heritage that will attract tourist visits. In addition to the tourism base, this location also has the potential of the creative economy industry. The Malang City Government itself has formed a Tourism Awareness Group (Pokdarwis) to develop tourism and the creative economy of this region. Unfortunately, until now there has been no effective marketing strategy to develop Kampoeng Heritage Kajoetangan. People in this area are not yet fluent in marketing virtually or through online media. For this reason, the dedication team from Brawijaya University conducts virtual marketing training. This community service activity aims to increase knowledge, especially for the management of Pokdarwis Kampoeng Heritage Kajoetangan regarding technical marketing online and through the website. This method of implementing community service is carried out through online media, providing an explanation of the importance of online marketing in the current pandemic era through lectures, discussions and training. Through this training, community service participants become knowledgeable about the importance of online marketing. In addition, participants become aware of online websites to sell and promote their products.